Subcutaneous implantable cardioverter defibrillator in cardiomyopathies and channelopathies. Issue 11 (November 2018) - Migliore, Federico; Pelliccia, Francesco; Autore, Camillo; Bertaglia, Emanuele; Cecchi, Franco; Curcio, Antonio; Bontempi, Luca; Curnis, Antonio; De Filippo, Paolo; D'Onofrio, Antonio; Francia, Pietro; Maurizi, Niccolò; et al.
Abstract : N/A: Cardiomyopathies and channelopathies are heterogeneous disorders that increase the risk of sudden cardiac death (SCD). Implantable cardioverter-defibrillator (ICD) therapy is safe and effective for preventing SCD in patients at risk for malignant ventricular arrhythmias. Because of the poor positive predictive value of current risk stratification tools, the majority of patients implanted with an ICD will never receive a life-saving therapy but will be exposed to the risk of complications such as device infection, lead failure and inappropriate therapy. Subcutaneous ICD (S-ICD) now constitutes a valuable alternative to conventional transvenous ICD in patients with cardiomyopathies and channelopathies as it provides protection from SCD while avoiding the risks of intravascular lead infection or failure. This may be particularly advantageous for young patients with a very long life expectancy. On the other hand, S-ICD cannot deliver antitachycardia pacing or antibradycardia pacing. The purpose of this article is to review the available evidence and the future perspectives of S-ICD therapy in patients with cardiomyopathies or channelopathies.